Factors associated with attempted suicide during adolescence - Sacoor, Sherbanu Noormahomed (My University, 2015)
This study examines factors associated with attempted suicide during adolescence. The sample consists of 10 Black adolescent girls who atempted suicide in the past year, and were admitted to Baragwanath Hospital. Each subject was questioned on demographic information and completed the Separation Anxiety Test (Hansburg, 1972) and Section 1 of the Inventory of Parent and Peer Attachment (Armsden and Greenberg, 1987), which assesses attachment to a parent. Subjects were also required to answer questions on their choice of responses. Common trends were found to exist among adolescent girls who attempt suicide. Adolescent girls who attempt suicide have disruptive home environments where parents experience marital problems. They show a low degree of attachment, high degree of hostility, stress avoidance during the stage of identity crisis, and they maintain a poor attachment-individuation balance. These findings suggest that the most common treatment strategy, ie. crisis intervention is not sufficient as it does not deal with underlying problems of adolescent suicide.
Thesis (M.A.)--University of the Witwatersrand, Faculty of Humanities, 1991.
Keywords: Suicidal behavior -- South Africa; Self-destructive behavior; Teenagers -- suicidal behavior -- South Africa